GERAKAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DALAM PEMBERDAYAAN WANITA DI DESA TEGAL ARUM TAHUN 2017-2019 - Miranti Miranti; Hariska Yuanita Sari (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
Family Welfare Empowerment is one of the community organizations and plays a very important role in community empowerment. This study aims to reveal the form of family welfare empowerment activities in empowering women. This research was conducted in Tegal Arum Village, Rimbo Bujang District, Tebo Regency, Jambi Province. The empowerment implemented by the PKK in Tegal Arum Village is in the form of empowering life skills, namely the PKK chairman provides guidance, provides skills equipment, and conducts training, as well as marketing. Furthermore, PKK in spiritual development held regular recitations and grand yasinan. In terms of health empowerment, PKK holds a posyandu every month for toddlers and the elderly. In toddlers holding immunizations, giving milk to toddlers, and providing additional food (PMT). While for the elderly, namely conducting counseling on healthy lifestyles, holding health checks. In Tegal Arum Village in the field of working group I, namely the practice and appreciation of Pancasila and mutual cooperation, the PKK Mobilization Team holds regular recitations of pahingan once a month and holds regular recitations every Friday, and carries out community service cleaning the posyandu yards and the yard in Tegal Arum Village . In the field of working group II, namely education and skills programs as well as the development of cooperative life, the PKK Mobilization Team carries out the UP2K field, namely the skills field, by processing handicrafts and processed foods such as stick plates, sweet potato chips and lunkhead. In the field of working group III, namely food, clothing, housing and household management, the Tegal Arum Village PKK Mobilizing Team formed a group of youths to manage vacant land in Tegal Arum Village. In the areas of working group IV, namely health, environmental sustainability, and healthy planning, the PKK Mobilizing Team carries out outreach to the community related to community needs.